2019
DOI: 10.1007/s00127-019-01725-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of neuroticism in self-harm and suicidal ideation: results from two UK population-based cohorts

Abstract: BackgroundSelf-harm is common, debilitating and associated with completed suicide and increased all-cause mortality, but there is uncertainty about its causal risk factors, limiting risk assessment and effective management. Neuroticism is a stable personality trait associated with self-harm and suicidal ideation, and correlated with coping styles, but its value as an independent predictor of these outcomes is disputed.MethodsPrior history of hospital-treated self-harm was obtained by record-linkage to administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 87 publications
3
11
0
Order By: Relevance
“…An association of neuroticism with increased suicidal behavior risk has already been described in population-based cohorts [14,28,29] and studies on individuals with personality [30] or affective disorders [31][32][33]; our secondary analyses confirmed these findings in patients with MDD (the largest diagnostic group in our study) and showed similar effects for BD and SCZ, suggesting that neuroticism may represent a transdiagnostic risk factor for SI [34].…”
Section: Discussionsupporting
confidence: 89%
“…An association of neuroticism with increased suicidal behavior risk has already been described in population-based cohorts [14,28,29] and studies on individuals with personality [30] or affective disorders [31][32][33]; our secondary analyses confirmed these findings in patients with MDD (the largest diagnostic group in our study) and showed similar effects for BD and SCZ, suggesting that neuroticism may represent a transdiagnostic risk factor for SI [34].…”
Section: Discussionsupporting
confidence: 89%
“…The results confirm that internalizers exhibit a greater negative affect than externalizers and report a greater symptoms disturbance, in line with the results of research linking neuroticism with NA (Gómez et al, 2002;Gross et al, 1998;Meyer and Shack, 1989;Uziel, 2006) and with psychopathology (Lahey, 2009;Hafferty et al, 2019;Ormel et al, 2013). Griffith et al (2010) came to find an almost perfect correlation between internalization and neuroticism.…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, if neuroticism is a relatively stable trait for years (which makes it possible to predict vulnerability to adversity), task-focused learning of coping strategies is an important protective factor that should be strengthened (Hafferty et al, 2019). This introduces us to the comment on the finding that we consider most relevant in this work: the use of favourable coping strategies (rational and detached styles) could alleviate the effect that personality (directly and through affective disposition) exerts on distress and pathology.…”
Section: Discussionmentioning
confidence: 99%
“…The association between the immune system and mental health may be different in females and in males [13,56,57], although the reasons for this are still unclear, leading to a question whether gender differences may exist in the effect of infections on suicidality. As transmission of CMV requires intimate contact with other people, one could speculate whether persons seronegative for CMV have personality factors that predispose to suicidality as well, such as neuroticism [58] or social isolation. However, HSV-1 and EBV have similar modes of person-to-person transmission as CMV, and our result was specific to CMV.…”
Section: Discussionmentioning
confidence: 99%